Dynamic inconsistency, commitment, and welfare in strategic settings - Asen Ivanov (Queen Mary University of London, School of Economics and Finance, 2023)
The choices of a dynamically inconsistent individual depend on whether she commits to consumption ahead of time or chooses consumption in the moment. In individual-choice settings, it is normatively ambiguous whether such an individual's choices with commitment or in the moment are "better". This impasse can be overcome in settings in which dynamically inconsistent individuals interact strategically. Policy implications are discussed.
Keywords: D60; D90; 330; dynamic inconsistency; commitment; welfare